Car-car wifi: measurement and analysis of communication quality in busy channel - Ong, Jocelyn Li Ting (2017)
Dedicated Short Range Communication (DSRC) is an upcoming technology that has been widely researched on in the recent years as a potential solution to reduce traffic accidents. The demand of owning a personal vehicle for transportation has been increasing and the increase in number of vehicles on the road tend to cause more collisions due to human error with approximate 1.25 million death per year just from traffic accidents reported by the World Health Organization (WHO). DSRC is a technology that made use of a wireless communication channel specifically designed for vehicular communication applications. Such applications include collision avoidance, warning notification system, toll collection and much more. These work on a very simple concept of sending packets namely Basic Safety Messages (BSM). BSM contains useful information necessary for drivers to ensure a smooth journey, and in order for that to happen, research needs to be done on the channels the BSMs would be transmitted on and finding out the success rate of the packet transmitted and received. The signal transmission rate varies with the environment and the busy ratio of the channel. This report will cover the results obtained during measurements and testing on the channels based on how busy the channel is with a different number of users and how successful packets will be received in the busy channels. The report will also cover the Android application to analyse the Channel Busy Ratio of the channels in 5.9 GHz band and Received Signal Strength Index of each of the channel.